Ergonomic Risk Assessment and MSDs Symptoms Among Laboratory Workers Using SNI 9011-2021 - Kusumawardhani, Adinda; Djamalus, Hendra; Dani Lestari, Kartika (The Indonesian Journal of Occupational Safety and Health, 2023)
Introduction: Musculoskeletal Disorders (MSDs) symptoms are experienced by 1.71 billion of the human population and are characterized by persistent pain that decreases the ability to work in almost all types of occupations, including laboratory workers. The various stages of work in laboratory can cause complaints due to repetitive motions, manual handling, static and awkward posture, as well as long-duration of work. Therefore, this study aimed to determine risk level of work ergonomic and MSDs symptoms among laboratory workers. Methods: This study used a cross-sectional design involving 71 laboratory workers who were observed from 8 to 22 June 2022. The respondents were categorized into three Similar Exposure Group (SEG), namely administrative officers, analysts, and field workers. Risk level of MSDs symptoms and work ergonomic of each SEG was measured using the instrument of SNI 9011-2021, while individual factor was estimated through the questionnaire. Results: Out of the 71 respondents, the majority were males, aged <35 years, and had <5 years of work experience. The survey revealed that half of workers experienced MSDs symptoms with a high-risk level in analysts and field workers, particularly in the lower back. The highest MSDs symptoms in all SEG were neck, lower back, upper back, and right shoulder. Conclusion: Ergonomic risk level in laboratory was dangerous for analysts and field workers, and required further assessment by administrative officers. To reduce risk level of work ergonomic, particularly for analysts and field workers, engineering control and the use of manual handling equipment can be implemented.